advanced functions

posted by .

Prove that

cscx / cosx = tanx + cotx

  • advanced functions -

    LS = cscx/cosx
    = (1/sinx)/cosx
    = 1/(sinxcosx)

    RS = sinx/cosx + cosx/sinx
    = (cos^2x + sin^2x)/(sinxcosx)
    = 1/(sinxcosx)
    = LS

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Math

    Verify the identity . (cscX-cotX)^2=1-cosX/1+cosX _______ sorry i cant help you (cscX-cotX)=1/sinX - cosX/sinX = (1-cosX)/sinX If you square this you have (1-cosX)^2/(sinX)^2 Now use (sinX)^2 = 1 - (cosX)^2 to get (1-cosX)^2 / 1 - …
  2. Math

    1)A piano tuner uses a tuning fork. If middle C has a frequency of 264 vibrations per second, write an equation in the form d=sinw(t) for the simple harmonic motion. 2) Verify the identity tan^2X-cot^2X/tanX+cotX=tanX-cotX I'm not …
  3. trig

    express this in sinx (1/ cscx + cotx )+ (1/cscx- cotx) i got 2sinx is that right?
  4. drwls

    My previous question: Verify that (secx/sinx)*(cotx/cscx)=cscx is an identity. (secx/sinx)*(cotx/cscx) = (secx/cscx)(cotx/sinx) = (sinx/cosx)*cotx*(1/sinx) "The last steps should be obvious" Not to me. I can convert (sinx/cosx) to …
  5. Pre-Calculus

    Find a numerical value of one trigonometric function of x if tanx/cotx - secx/cosx = 2/cscx a) cscx=1 b) sinx=-1/2 c)cscx=-1 d)sinx=1/2
  6. Trig

    Prove the following functions: (sinx+sin2x)/(1+cosx+cos2x)=tan x (cos3x/sinx)+(sin3x/cosx)=2cot2x tan2x=(2/cotx-tanx) theses are due in the am. Fastness would be great?
  7. Math

    Im really struggling with these proving identities problems can somebody please show me how to do these?
  8. Math

    Im really struggling with these proving identities problems can somebody please show me how to do these?
  9. Math

    I'm only aloud to manipulate one side of the problem and the end result has to match the other side of the equation Problem 1. sinx + cosx + sinx + tanx + cosxcotx = secx + cscx Problem 2. ((sinx + cosx)/(1 + tanx))^2 + ((sinx - cos^2x)/(1 …
  10. Precalculus/Trig

    I can't seem to prove these trig identities and would really appreciate help: 1. cosx + 1/sin^3x = cscx/1 - cosx I changed the 1: cosx/sin^3x + sin^3x/sin^3x = cscx/1-cosx Simplified: cosx + sin^3x/sin^3x = cscx/1-cosx I don't know …

More Similar Questions